Cartel pricing dynamics in the presence of an antitrust authority - Joseph E. Harrington (The Johns Hopkins University, Department of Economics, 2002)
Price-fixing is characterized when firms are concerned about creating suspicions that a cartel has formed. Antitrust laws have a complex effect on pricing as they interact with the conditions determining the internal stability of the cartel. Dynamics are driven by two forces - the sensitivity of detection to price movements causes a cartel to gradually raise price while the sensitivity of penalties to the price level induces the cartel to lower price over time in order to maintain the stability of the cartel. While antitrust laws can lower collusive prices, they can also raise them by making it easier for firms to collude.
Keywords: L1; L4; 330; Collusion; Cartel Detection; Antitrust; Kartell; Betriebliche Preispolitik; Konzentrationspolitik; Verhandlungstheorie